Analysis of competitive anxiety levels among the age group 4–5 swimming athletes - Pandu Kurnia Sujiwo; Shinta Masitho Windriyani; Anangga Widya Pradipta; Rubbi Kurniawan (Universitas Sriwijaya, 2026)
Research Problems: Anxiety is one of the psychological factors that can affect athletes' performance during competition. Young athletes are more susceptible to competitive anxiety due to limited competitive experience, underdeveloped emotional regulation, and increasing demands to achieve high performance. Therefore, identifying athletes' anxiety levels is essential as a basis for developing effective mental training programs. Research Objectives: This study aimed to describe the level of competitive anxiety among swimming athletes in Age Groups (AG) 4 and 5 as a foundation for designing more effective mental training programs. Methods: This study employed a quantitative descriptive approach to examine the competitive anxiety levels of swimming athletes in Age Groups (AG) 4 and 5 during competition. The sample consisted of 38 athletes, including 20 males and 18 females. Data were collected using the Sport Development Tools Measuring Anxiety (SDTMA) questionnaire and analyzed descriptively using frequency and percentage distributions. Results: The findings revealed that 24 athletes (63%) were classified as having moderately low anxiety, 8 athletes (21%) had moderately high anxiety, and 6 athletes (16%) had low anxiety. No athletes were categorized as having high or very high anxiety. These results indicate that most athletes demonstrated a relatively good ability to manage competitive anxiety before and during competition. Conclusion: Overall, the competitive anxiety level of swimming athletes in Age Groups 4 and 5 was categorized as moderately low. Nevertheless, regular psychological monitoring and the implementation of structured mental training programs by coaches and sports psychology professionals remain necessary to help athletes manage competitive anxiety effectively, thereby optimizing their performance and competitive achievement.